The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3390/ph7040453
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, In Vitro and In Vivo Evaluation of the N-ethoxycarbonylmorpholine Ester of Diclofenac as a Prodrug

Abstract: The N-ethoxycarbonylmorpholine moiety was evaluated as a novel prodrug moiety for carboxylic acid containing drugs represented by diclofenac (1). Compound 2, the N-ethoxycarbonylmorpholine ester of diclofenac was synthesized and evaluated as a potential prodrug. The stability of the synthesized prodrug was evaluated in solutions of pH 1 and 7.4, and in plasma. The ester’s half lives were found to be 8 h, 47 h and 21 min in pH 1, pH 7.4 and plasma, respectively. Equimolar doses of diclofenac sodium and its synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The prodrug synthesized N-ethoxycarbonylmorpholine ester of diclofenac (Fig. 107 ) [ 93 ]. The stability of the prodrug was evaluated in buffer solution and in plasma.…”
Section: Resultsmentioning
confidence: 99%
“…The prodrug synthesized N-ethoxycarbonylmorpholine ester of diclofenac (Fig. 107 ) [ 93 ]. The stability of the prodrug was evaluated in buffer solution and in plasma.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that this is the first attempt that compares the antipyretic effectiveness of the rectal forms of Paracetamol and Diclofenac. Diclofenac is rapidly absorbed in those parts of the gastrointestinal tract that have pH values higher than five ( 23 ). Paracetamol is also highly absorbed under alkaline conditions; however, its absorption is less dependent on the environmental pH ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…90). 304 The prodrug exhibited good intrinsic chemical stability, with t 1/2 values of 8 h and 47 h at pH 1.0 and 7.4, respectively, but degraded more readily in human plasma, with a t 1/2 of 21 min. This indicated that the prodrug would have sufficient stability in the GI tract to ensure intact absorption, while undergoing rapid activation in the plasma by esterases to release the parent.…”
Section: Design Of Prodrugs That Mitigate Toxicity For Non-oncology I...mentioning
confidence: 95%